Organic cultivation of turmeric by Good Agricultural Practices (GAP) in Bundelkhand region - Dayal, Guru; Singh, Satyavir; Pahade, Ekanshu (Indian Farming, 2023)
The major aim of the turmeric cultivation is due to its properties such as antibiotic, antioxidant, anti-inflammatory, antimicrobial, antitumor, cepto-protective (to protect the liver), cardioprotective (to protect the heart) etc. which proves as very useful for curing various diseases. Turmeric powder is used as spices since a very long time. The essential component present in turmeric is known as curcumin which has many medicinal properties. It also has some amount of essential oils, which is volatile in nature. This crop is very useful and the beneficiary results can be brought by following the scientific methods of cultivation, such as good agricultural practices(GAP). This crop has been proven very useful for the farmers continuing their agriculture practices in a barren land. Also the farmer’s can produce quite a good income by the cultivation of this crop.